Избирательное сродство в социологии Макса Вебера - Кутуев, П. (Социология: теория, методы, маркетинг, 1999)
Although being central to the understanding Weber’s idea of interpretative socialsciences, the notion of elective affinity is conspiciously absent from sociological theory debates, especially in Ukraine. This paper offers a systematic account of “elective affinity” in Weber’s corpus. The essay traces the history of the term fromchemistry through philosophy and literature to Weber’s sociology drawing upon Weber’s sporadic and unsystematic usage and application of “elective affinity” in “Economy and Society” as well as his studies on sociology of religion and domination. The article is seeking to demonstrate that the concept of elective affinity enabled Weber to appreciate the autonomous nature of societal spheres and develophis theorizing against the backdrop of modern sociology. Contrary to the assumptions of historical materialism, Weber held that economic determination of social action isambiguous since the forms of social action follow “laws of their own”. Thus, according to Weber, the social scientist can generalize about the degree of elective affinity between concrete structures of social action and concrete forms of economic organization. In other words, the scholar can only state whether the phenomena in question are “adequate” or “inadequate” in relation to one another.